2018
DOI: 10.1186/s12916-018-1153-0
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare service delivery to refugee children from the Democratic Republic of Congo living in Durban, South Africa: a caregivers’ perspective

Abstract: BackgroundRefugees are generally considered a vulnerable population, with refugee children (newborn and young children) being particularly so. Access to healthcare for this population remains a challenge. The main purpose of this study was to explore refugee caregivers’ perceptions of their children’s access to quality health service delivery to their young children in Durban, South Africa.MethodsThis study used an explanatory mixed methods design, purposively sampling 120 and 10 participants for the quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Eight of the studies included in this review analyse health care services [ 119 , 123 , 207 , 208 , 209 , 210 , 211 , 212 ]. AMC in the UK indicate not having contact with health care services [ 123 ]; AMC in Israel adopt Western practices and go to the clinic for medical treatment, but if this does not prove satisfactory, they seek out solutions according to familiar patterns from their country of origin for medical, social, or emotional problems [ 207 ]. Similarly, AMC caregivers in South Africa report dissatisfaction with health care services [ 208 ], and AMC in Spain report a sense of pointlessness in seeking out health care services [ 209 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight of the studies included in this review analyse health care services [ 119 , 123 , 207 , 208 , 209 , 210 , 211 , 212 ]. AMC in the UK indicate not having contact with health care services [ 123 ]; AMC in Israel adopt Western practices and go to the clinic for medical treatment, but if this does not prove satisfactory, they seek out solutions according to familiar patterns from their country of origin for medical, social, or emotional problems [ 207 ]. Similarly, AMC caregivers in South Africa report dissatisfaction with health care services [ 208 ], and AMC in Spain report a sense of pointlessness in seeking out health care services [ 209 ].…”
Section: Resultsmentioning
confidence: 99%
“…While many of the studies included children as data sources, these were overwhelmingly quantitative. Only 10 studies were qualitative and gathered data from migrant and refugee children from countries in sub-Saharan Africa [ 112 , 116 , 120 , 124 , 125 , 129 , 132 , 150 , 166 , 207 ]. The rest of the qualitative studies gathered data about children from parents or service provider participants.…”
Section: Discussionmentioning
confidence: 99%
“…It is substantially documented in the research literature that refugees and migrants are a highly vulnerable population experiencing many difficulties and stressors in their sojourns for a safe haven (Meyer-Weitz, Asante, & Lukobeka, 2018;Idemudia et al 2013;Bustamante et al, 2018). Given that the migration process is accompanied with a myriad of stressors, trauma and psychological difficulties, it is necessary to understand the strategies adopted by migrants to cope with these problems in order to prevent exacerbation of associated mental health problems.…”
Section: Coping Mechanisms and Migrants' Adaptationmentioning
confidence: 99%
“…In a study in Durban, South Africa, Meyer-Weitz et al [ 3 ] explored the health access perception of predominantly female caregivers of Congolese refugee children and concluded that long waiting times, negative attitudes, and discrimination are key sources of dissatisfaction with primary healthcare. By contrast, in Australia, an analysis of longitudinal data to investigate levels of post migration psychological adjustment among refugee children concluded that the majority of resettled children and adolescents was well adjusted, especially those with better physical health and school attendance, although young refugees reported greater peer difficulties [ 4 ].…”
Section: Refugee Healthmentioning
confidence: 99%